MiR-221/222 activate the Wnt/β-catenin signaling to promote triple-negative breast cancer. (25th August 2018) - Liu, Sanhong; Wang, Zifeng; Liu, Zukai; Shi, Shuo; Zhang, Zhaoran; Zhang, Jiawei; Lin, Haifan
Abstract: Triple-negative breast cancer (TNBC), characterized by the lack of expression of the estrogen receptor, the progesterone receptor, and the human epidermal growth factor receptor 2, is an aggressive form of cancer that conveys unpredictable and poor prognosis due to limited treatment options and lack of effective targeted therapies. Wnt/β-catenin signaling is hyperactivated in TNBC, which promotes the progression of TNBC. However, the molecular mechanism of Wnt/β-catenin activation in TNBC remains unknown. Here, we report the drastic overexpression of miR-221/222 in all of four TNBC cell lines and TNBC primary tumor samples from patients. Furthermore, we demonstrate by both ex vivo and xenograft experiments that inhibiting miR-221/222 expression in a TNBC cell line (MDA-MB-231) suppresses its proliferation, viability, epithelial-to-mesenchymal transition, and migration; whereas expressing miR-221/222 in a non-TNBC line (MCF7) promotes all of the above cancer properties. miR-221/222 achieve so by directly repressing multiple negative regulators of the Wnt/β-catenin signaling pathway, including WIF1, SFRP2, DKK2, and AXIN2, to activate the pathway. Notably, the level of miR-221/222 expression is inversely correlated whereas that of WIF1, DKK2, SFRP2, and AXIN2 expression is positively correlated with the patient survival. Last, we show that anti-miR-221/222 significantly increases apoptotic cells with tamoxifen/Wnt3a treatment but not with cyclophosphamide/Wnt3a treatment. These results demonstrate that miR-221/222 activate the Wnt/β-catenin signaling to promote the aggressiveness and TNBC properties of breast cancers, and thus reveal a new prospect for TNBC treatment.